Efeito de sistemas de cultivo na fitossociologia, no banco de sementes de plantas daninhas e nos componentes de rendimento do feijão, milho e soja - Forte, César Tiago (2017)
In Brazil, beans, maize and soybeans stand out among the most sown annual crops in the summer, which directly or indirectly make up the Brazilian's food. Their cultivation methods and management practices are fundamental to reach the productive potential of crops. Among the management practices, stand out the systems of planting, right and / or conventional, which can somehow cause negative or positive impacts on the yield of beans, corn and soybeans. Use of soil cover and efficient pest management are other practices necessary for better crop production. The objective of this work was to evaluate whether soil management, with or without vegetation cover, modify phytosociological characteristics, seed germination and weed emergence, and yield components of bean, corn and soybean crops. Thus, field experiments were conducted between 2013 and 2016, in a randomized complete block design, using winter cover crops (black oats, vetch, turnip and consortium) and annual summer (beans, corn and soybean), in the conventional and no-tillage system. We evaluated the phytosociology of weeds present in the crops, the weed seed bank in the soil and the yield components related to the summer crops. The weed phytosociology was influenced by the cropping systems, interfering in the number of species found, and the conventional planting system favored the species Lolium multiflorum, but decreased the presence of Euphorbia heterophylla. It should be noted that the amount of dry mass produced by the cover crops is an excellent way of reducing the number of weed species in the growing areas. The seed bank of weeds and influenced by the management adopted in no - tillage systems increased the density of Gnaphalium spicatum and Oxalis corniculata, in contrast, decreased of Lolium multiflorum. For the weed seed bank the no-tillage system concentrates the seeds of the species in the superficial layers of the soil, reducing the seed bank in deeper layers. Already the conventional planting system distributes seeds along the soil profile, by the process of stirring. Bean was the crop less affected by the soil rotation, since corn reached the best grain yield when under no-tillage compared to the conventional tillage system. The same result was found for soybeans. The no-tillage system was more efficient for weed management and crop yield, especially corn and soybean, when compared to the conventional tillage system.